Sistem Manajemen Pariwisata di Kabupaten Bangka Menggunakan Teknologi Informasi - Dony Yanuar; Ghiri Basuki Putra (Jurnal Serambi Engineering, 2021)
Tourism area is expected to provide multiplier effects that encourage economic growth in Bangka Regency beside tin mining and farming. For a better way of managing of tourist destinations, preparation   of various aspects is required and the preparations are getting ready  for development of tourism in Bangka Regency area, especially the use of information technology and the Internet. In this study, the main key for  managing tourism based on information technology  is the management of tourist destinations in Bangka Regency, such as Matras Beach, Tongaci Beach, Tikus Mas Beach, Puri Tri Agung and so on which can be used as an interesting and unique destination for tourists to visit. Tourism management using information technology, especially Internet and android applications for tourism management in Bangka Regency to make it better and easier for both the government and tourists for controlling the data about tourism. This system is built using the System Development Life Cycle (SDLC) for make the system built correctly. The purpose is to  manage the tourism system  effectively and by using  Internet and Android, many people can  get informed about tourist attractions in Bangka Regency so  it is to be hoped that many people are interested in visiting tourist attractions in Bangka Regency. This tourism management aims to facilitate the delivery of tourist information and management of tourism destinations in Bangka Regency to make tourists easier and more comfortable when on trips in Bangka Regency.